The business strategy game - Thompson, Arthur A., 1940-; Stappenbeck, Gregory J. (Chicago : Irwin, 1997)
A business simulation involving the athletic footware industry. Students are required to devise five-year strategic plans, financial projections, and assess the revenue-cost profit consequences of alternative strategic actions.
Title from disk label.
Contains 1 company program disk and 1 company data disk.
System requirements: PC with 66 MHz 486DX2 processor; 8MB RAM; Windows 3.1 or Windows 95; one high-density 3 1/2 in. floppy disk drive; 6MB free file storage space on the fixed disk drive; printer access.
Keywords: Corporations -- Finance -- Computer simulation -- Software; Industrial management -- Computer simulation -- Software